2021
DOI: 10.1021/acsomega.1c01123
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Selective Catalytic Reduction of NOx with NH3 over Mn–Ce Composites Synthesized by Polymer-Assisted Deposition

Abstract: The Mn x Ce y binary catalysts with a three-dimensional network structure were successfully prepared via a polymer-assisted deposition method using ethylenediaminetetraacetic acid and polyethyleneimine as complexing agents. The developed pore structure could facilitate the gas diffusion and accelerate the catalytic reaction for NH3 selective catalytic reduction (SCR). Moreover, the addition of Ce is beneficial for the exposure of active sites on the catalyst surface and increases the adsorption of the NH3 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…122 It should be underlined that most of the low-temperature NH 3 -SCR of NO reported in the following table on MOF-based catalyst were performed using weight hourly space velocity (WHSV) equivalent to the tests carried out with mixed oxides or zeolite-based catalysts. 27,123,124 The mechanisms associated with these catalysts are similar to those reported generally for mixed oxide catalysts. 27 The SCR studies carried out on unmodified and modified MOFs, reported so far, clearly show the potential of this type of materials.…”
Section: Selective Catalytic Reduction Process (Scr)supporting
confidence: 78%
“…122 It should be underlined that most of the low-temperature NH 3 -SCR of NO reported in the following table on MOF-based catalyst were performed using weight hourly space velocity (WHSV) equivalent to the tests carried out with mixed oxides or zeolite-based catalysts. 27,123,124 The mechanisms associated with these catalysts are similar to those reported generally for mixed oxide catalysts. 27 The SCR studies carried out on unmodified and modified MOFs, reported so far, clearly show the potential of this type of materials.…”
Section: Selective Catalytic Reduction Process (Scr)supporting
confidence: 78%
“…This manifested that construction of the CeO 2 shell could effectively promote the catalytic performance. However, excessive CeO 2 did not seem to be conducive to improving the NH 3 -SCR performance and could cause a reduction of the catalytic performance because of the overthick CeO 2 shell covering some surface active sites . As shown in Figure S1, MnFe@CeO x -60 had excellent catalytic activity compared to the MnFeCeO x composite oxide catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…The oxidation of SO 2 caused the deposition of (NH 4 ) 2 SO 4 /NH 4 HSO 4 and metal sulfates on the catalysts. 29,30 Given that the more reducible metal oxides facilitated the formation of sulfates, it was reasonable to see that more sulfates had formed on the MnO x surface. So, the accumulated sulfates blocked the active sites and deactivated the redox properties, especially at low temperature.…”
Section: Performance Of the Catalystsmentioning
confidence: 99%
“…The stability tests in the presence of SO 2 and H 2 O were also carried out at 100 °C over time (Fig.S1, ESI †), and Mn-Fe-0.2 still displayed better SO 2 and H 2 O resistance than Mn 2 O 3 .The presence of SO 2 led to a decrease in the activity in the low temperature zone (<200 °C), whereas various performances were observed on the different samples at high temperature (300 °C). The oxidation of SO 2 caused the deposition of (NH 4 ) 2 SO 4 /NH 4 HSO 4 and metal sulfates on the catalysts 29,30. Given that the more reducible metal oxides facilitated the formation of sulfates, it was reasonable to see that more sulfates had formed on the MnO x surface.…”
mentioning
confidence: 99%